Radical Blake - Dent, S. author. aut Link
XIII, 237 p.
Keywords: Blake has maintained an enduring popularity amongst a large and diverse audience as a poet, artist and engraver. There are probably more artists, writers, filmmakers and composers working under the influence of Blake than any other figure from the Romantic era. Radical Blake traces his influence and afterlife across a range of major themes such as Metropolitan Blake, Blake and Nationalism, and Blake and Women.